Clostridium difficile Peritonitis: An Emerging Infection in Peritoneal Dialysis Patients - Saira Chaughtai; Bhavika Gandhi; Zeeshan Chaughtai; Dana Tarina; Mohammad A. Hossain; Arif Asif (Case Reports in Medicine)
Recently, the incidence of Clostridium difficile- (C. difficile-) associated infection has increased significantly in hospital and ambulatory care settings in parallel to the increasing use of inappropriate antibiotics. According to the CDC, approximately 83,000 patients who developed C. difficile experienced at least one recurrence and 29,000 died within 30 days of the initial diagnosis. Patients on dialysis (particularly peritoneal dialysis) are predisposed to this infection due to an inherent immunocompromised state and transmural translocation of the bacteria due to the close association of gastrointestinal tract and peritoneal cavity. C. difficile infection in peritoneal dialysis patients is problematic from two aspects: (1) because dialysis patients are immunocompromised, the infection can be devastating and (2) infection directly interferes with their renal replacement therapy. In this article, we present a case of peritoneal dialysis (PD)-related peritonitis caused by C. difficile-associated diarrhea and colitis. In this patient, the peritonitis was caused by transmural translocation of the enteric bacteria. While the peritoneal fluid culture did not grow the organism (possibly because of prior empiric broad-spectrum antibiotics use), the positive PCR on stool analysis suggested C. difficile-related peritonitis, along with the rapid clinical improvement induced by C. difficile-directed therapy (metronidazole) and discontinuation of broad-spectrum antibiotics. The patient was successfully treated with metronidazole without PD catheter removal. C. difficile infection is common and frequently internists are the first contact with such patients. This article highlights C. difficile infection in a PD patient and raises awareness of this infection in dialysis patients.